2010
DOI: 10.1128/jb.01676-09
|View full text |Cite
|
Sign up to set email alerts
|

The BatR/BatS Two-Component Regulatory System Controls the Adaptive Response ofBartonella henselaeduring Human Endothelial Cell Infection

Abstract: Here, we report the first comprehensive study of Bartonella henselae gene expression during infection of human endothelial cells. Expression of the main cluster of upregulated genes, comprising the VirB type IV secretion system and its secreted protein substrates, is shown to be under the positive control of the transcriptional regulator BatR. We demonstrate binding of BatR to the promoters of the virB operon and a substrate-encoding gene and provide biochemical evidence that BatR and BatS constitute a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 60 publications
7
89
0
Order By: Relevance
“…We chose B. henselae as a model system for several reasons: (1) Its relatively small genome (1.93 Mbp) comprises 1488 predicted protein-coding genes (Alsmark et al 2004); (2) it is a facultative intracellular pathogen that can be grown in pure culture; (3) protocols for subcellular fractionation have been described (Rhomberg et al 2004); and (4) in vitro conditions that mimic the pH-dependent induction of virulence genes required for the successful interaction with host endothelial cells, the likely primary niche for B. henselae (Harms and Dehio 2012), have been established (Quebatte et al 2010). The availability of a model system that eliminates the need for coculture with human endothelial cells is critical to achieve complete coverage of an expressed proteome.…”
Section: Resultsmentioning
confidence: 99%
“…We chose B. henselae as a model system for several reasons: (1) Its relatively small genome (1.93 Mbp) comprises 1488 predicted protein-coding genes (Alsmark et al 2004); (2) it is a facultative intracellular pathogen that can be grown in pure culture; (3) protocols for subcellular fractionation have been described (Rhomberg et al 2004); and (4) in vitro conditions that mimic the pH-dependent induction of virulence genes required for the successful interaction with host endothelial cells, the likely primary niche for B. henselae (Harms and Dehio 2012), have been established (Quebatte et al 2010). The availability of a model system that eliminates the need for coculture with human endothelial cells is critical to achieve complete coverage of an expressed proteome.…”
Section: Resultsmentioning
confidence: 99%
“…Infections of Ea.hy926 (to measure DNA transfer) and Ea.hy926/pRS56-c#B1 cells (to measure protein transfer) with B. henselae strains were performed as described (19,21), and the multiplicity of infection (34) and duration of infection were as indicated in the text and figure legends. The higher protein transfer rates obtained in the present work versus the rates obtained previously (19) are related to the use of M199/10% FCS growth medium instead of DMEM/10% FCS during the infection, resulting in a higher activation of the VirB/VirD T4SS (40). After infections, cells were trypsinized, recovered in growth medium, and 4 × 10 4 to 1 × 10 5 cells were analyzed by using a FACSCalibur flow cytometer (Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we performed adhesion-and translocation-independent invasome formation, testing different Bhe mutant strains. In addition to wildtype Bhe, we used the effector-free deletion strain Bhe DbepA-G, the Bhe DvirB2-11 mutant strain carrying a deletion of the entire virB/D4 T4SS locus and the Bhe DbatR strain with an in-frame deletion in the transcriptional response regulatory protein BatR, which together with the sensor histidine kinase BatS, is known to form a two-component regulatory system controlling pH-regulated expression of several Bhe virulence genes, including the genes of the virB/D4 locus and the adjacent bep effector loci (Quebatte et al, 2010). The results showed that adhesion to GD25 b1A cells as well as translocation-independent invasome formation was not affected by the deletion of either the bep effector loci or the virB/ D4 T4SS locus (Fig.…”
Section: Several Components Associated With Integrin-mediated Signalimentioning
confidence: 99%